Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Dewan Komisaris Independen, Komite Audit, dan Konflik Bondholders-Shareholders Terhadap Konservatisme Akuntansi - Naufal, M. Fakhri Adli; Susilowati, Retno Yuni Nur; Sudrajat, Sudrajat; Azhar, Rialdi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine the effect of institutional ownership, managerial ownership, independent board of commissioners, audit committee, and bondholders-shareholders conflict on property and real estate companies listed on the Indonesia Stock Exchange in 2018-2022. This research is a type of quantitative research using secondary data from the Indonesia Stock Exchange and the official website of each company. The sample determination method used purposive sampling and obtained a sample of 23 companies with an observation period of 5 years so that the total research sample was 111 data. The data analysis technique used is multiple linear regression using SPSS 27 software. Based on the research results, it was found that institutional ownership, managerial ownership, independent board of commissioners, audit committee and bondholders-shareholders conflict simultaneously affect accounting conservatism. Partially, the independent board of commissioners has a positive effect on accounting conservatism and the audit committee has a negative effect on accounting conservatism. However, this study did not find any influence between the variables of institutional ownership, managerial ownership, and bondholders-shareholders conflict on accounting conservatism.